Studi Konfigurasi Ruang Mall (Studi Kasus: Matahari Mall dan Ayani Megamall di Pontianak) - Andi Andi; Zairin Zain; Uray Fery Andi (Universitas Sebelas Maret Surakarta, 2020)
Mall is a commercial building that prioritizes pedestrian concept and spatial relation. The assessment of spatial relation can be analyzed by using space syntax method. There is a significant difference in the visitor rate between Matahari Mall and Ayani Megamall which gives rise to a hypothesis that the spatial configuration affects the success of the mall. The purpose of this study is to determine the problems that exist in spatial configuration of the mall. This research uses a sequential explanatory approach that combines the space syntax method (choice simulation and gate count observation) with grounded theory analysis. Grounded theory analysis is done by comparing space syntax data with the theory of the mall. The data is analyzed with correlation analysis, to see the similitude of simulation data with field data. The result of this study is Ayani Megamall as the one with higher visitor rate has a better organized spatial configuration than Matahari Mall. This result has proven the hypothesis that spatial configuration affects the success of mall. The spatial configuration problems found are the placement of anchor, retail, and elevator which unable to support the visitor’s movement to all places.